2017
DOI: 10.1007/s00062-017-0568-x
|View full text |Cite
|
Sign up to set email alerts
|

Internal Carotid Artery Stenosis and Collateral Recruitment in Stroke Patients

Abstract: PurposeLeptomeningeal collaterals improve outcome in stroke patients. There is great individual variability in their extent. Internal carotid artery (ICA) stenosis may lead to more extensive recruitment of leptomeningeal collaterals. The purpose of this study was to evaluate the association of pre-existing ICA stenosis with leptomeningeal collateral filling visualized with computed tomography perfusion (CTP).MethodsFrom a prospective acute ischemic stroke cohort, patients were included with an M1 middle cerebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Currently, both methods are rater-dependent since they rely on visual rating scales. 57,58 Conventional collateral scores obtained from CTA and DSA did not show significant correlations with CVI PWI or clinical outcome measures at admission. This might be due to the fact that the scan duration of conventional CTA in some cases can be too short to detect collateral filling in the late venous phase and that the DSA-based collateral score used in this study is determined by unilateral angiographic examination of the affected side only and, therefore, might fail to capture the crossflow to leptomeningeal vessels from the contralateral unaffected side.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Currently, both methods are rater-dependent since they rely on visual rating scales. 57,58 Conventional collateral scores obtained from CTA and DSA did not show significant correlations with CVI PWI or clinical outcome measures at admission. This might be due to the fact that the scan duration of conventional CTA in some cases can be too short to detect collateral filling in the late venous phase and that the DSA-based collateral score used in this study is determined by unilateral angiographic examination of the affected side only and, therefore, might fail to capture the crossflow to leptomeningeal vessels from the contralateral unaffected side.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, also CTP can be used to directly assess leptomeningeal collateralization in acute stroke, using a time-resolved approach. 57,58 However, acquisition captures fewer images of the brain during bolus passage 57,58 than in MR DSC perfusion, leading to limitations regarding late collateral filling. Furthermore, there are issues around radiation dose when repeatedly imaging the brain during bolus arrival.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, when distinguishing distal and proximal segment of ICA occlusions, we found more patients with proximal segment of ICA occlusion and fewer patients with distal ICA occlusions achieved functional independence. The reason for this difference may be most of proximal segment of ICA occlusion were related to chronic stenosis possibly with a rich collateral network [ 36 ]. Consistent with previous studies, high ASPECTS score was demonstrated to be associated with functional independence of AIS patients after EVT in this study [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…As previous studies revealed, CTP scans were performed with the 64-slice detector CT scanner (Philips, Best, the Netherlands) and followed with injection of diluted nonionic contrast material. CTP data were then transferred to a postprocessing workstation (Extended Brilliance Workstation v 3.0, Philips Medical Systems) [ 22 ]. Cerebral blood volume (CBV), cerebral blood flow (CBF), mean transit time (MTT), and time to peak (TTP) were calculated using a deconvolution operation (Extend Brilliance Workstation v 3.0, Philips Medical Systems, USA).…”
Section: Methodsmentioning
confidence: 99%